Dual Class Stock in Russia: What Explains the Price Differential between Common and Preferred Shares? - Alexander Muravyev (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper aims to explain the large premium paid on common (voting) shares relative to preferred (non-voting) shares in the Russian stock market. Empirical analysis focuses on two main explanations relating the premium either to the voting right attached to common shares or to differences in liquidity between the two classes of stock. Two avenues through which the right to vote may give rise to the premium are distinguished. First, the presence of private benefits of control and the possibility of control contests may make the votes held by small investors pivotal, and therefore valuable. Second, non-voting shareholders may be expropriated as a class by voting shareholders. Regression analysis of RTS stock exchange data from 1997- 2005 provides support for the control contest model of the premium as well as for the liquidity argument. The study finds no evidence that the premium is related to expropriation of preferred shareholders as a class.
Keywords: G34; G32; 330; Börsenkurs; Stimmrecht (Gesellschaftsrecht); Vorzugsaktie; Börsenumsatz; Russland